South American sea lions (Otaria flavescens) and killer whales (Orcinus orca) attending chub mackerel (Scomber japonicus) commercial trawl fisheries over the Patagonian Shelf: a first report - Seco Pon, Juan Pablo; Favero, Marco (Latin American Journal of Aquatic Mammals)
Killer whale-seal interactions have been reported for almost all pinniped species globally. However the literature on offshore interactions between killer whales and sea lions is rare for the South Atlantic, particularly in Argentine waters. Here we report for the first time the harassment of a South American sea lion (Otaria flavescens) by killer whales (Ornicus orca) while attending commercial fishing vessels in offshore national waters and describe a novel sea lion antipredator behaviour. These observations were made during an ongoing survey to assess seabird-fisheries interactions in the commercial trawl fishery off Argentina. Fil: Seco Pon, Juan Pablo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Favero, Marco. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina